Review of valuation from a non-market perspective: travel cost method for rural tourism - Mohammad Afandi, Syamsul Herman; Samdin, Zaiton; Shuib, Ahmad (Emerald Group Publishing, 2013)
Purpose: The study aims to conduct a critical analysis of available economic tools to value non‐market rural tourism products and services, and assess the strengths and weaknesses of these tools. Design/methodology/approach: The paper reviews existing valuation methods to better understand how estimates of rural tourism products and services are conducted. The paper also critically evaluates the applicability of these methods.Findings: The study concludes that the selection of a method is mainly based on applicability of the approach. In assessing the non‐market value of rural tourism products and services, a method is selected by identifying its strengths and weaknesses. A review of previous studies suggests the evaluation of the practicality of each method according to the topic studied. Originality/value: The paper contributes to a better understanding of available valuation approaches that give reliable estimates on non‐market rural tourism products and services.